2020
DOI: 10.3390/w12030866
|View full text |Cite
|
Sign up to set email alerts
|

Estimating 500-m Resolution Soil Moisture Using Sentinel-1 and Optical Data Synergy

Abstract: The aim of this study is to estimate surface soil moisture at a spatial resolution of 500 m and a temporal resolution of at least 6 days, by combining remote sensing data from Sentinel-1 and optical data from Sentinel-2 and MODIS (Moderate-Resolution Imaging Spectroradiometer). The proposed methodology is based on the change detection technique, applied to a series of measurements over a three-year period (2015 to 2018). The algorithm described here as “Soil Moisture Estimations from the Synergy of Sentinel-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Spaceborne remote sensing (RS) provides spatially explicit information as satellites sense the same ground trace in regular time intervals, allowing for continuous monitoring (Babaeian et al, 2019). Estimates of θ are retrieved from different sensors measuring optical and thermal spectra (e.g., Rahimzadeh-Bajgiran et al, 2013;Zhang and Zhou, 2016), by passive and active microwave sensors (e.g., Schmugge and Jackson, 1997;Das and Paul, 2015), or the synergistic use of different sensor types such as using radar and optical data from Sentinel-2, Landsat, and MODIS (e.g., Attarzadeh et al, 2018;Ayehu et al, 2020;Foucras et al, 2020;Han et al, 2020;Ma et al, 2020). Synthetic Aperture Radars (SAR) are among the most effective and flexible active microwave sensor systems (e.g., Wang and Qu, 2009;Santi et al, 2016) due to their ability to penetrate the near-surface soil layer up to a depth of 5 cm (i.e., for C-band), which in turn enables to observe θ by directly relating the microwave scattering and emission to the water content of the focused object (e.g., Paloscia et al, 2013;Santi et al, 2016;Mohanty et al, 2017;Babaeian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Spaceborne remote sensing (RS) provides spatially explicit information as satellites sense the same ground trace in regular time intervals, allowing for continuous monitoring (Babaeian et al, 2019). Estimates of θ are retrieved from different sensors measuring optical and thermal spectra (e.g., Rahimzadeh-Bajgiran et al, 2013;Zhang and Zhou, 2016), by passive and active microwave sensors (e.g., Schmugge and Jackson, 1997;Das and Paul, 2015), or the synergistic use of different sensor types such as using radar and optical data from Sentinel-2, Landsat, and MODIS (e.g., Attarzadeh et al, 2018;Ayehu et al, 2020;Foucras et al, 2020;Han et al, 2020;Ma et al, 2020). Synthetic Aperture Radars (SAR) are among the most effective and flexible active microwave sensor systems (e.g., Wang and Qu, 2009;Santi et al, 2016) due to their ability to penetrate the near-surface soil layer up to a depth of 5 cm (i.e., for C-band), which in turn enables to observe θ by directly relating the microwave scattering and emission to the water content of the focused object (e.g., Paloscia et al, 2013;Santi et al, 2016;Mohanty et al, 2017;Babaeian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since irrigation eventually increases the soil and the vegetation water content, the sensitivity of the radar signal to soil and vegetation water could help detect these irrigation events. Through literature, it has been widely demonstrated that the SAR backscattering coefficient (σ 0 ) is directly related to the soil and vegetation water content [14][15][16][17][18][19][20]. Mainly for the irrigation task, Hajj et al [21] have reported that a three-day-old irrigation point could still be detected using X-band SAR data.…”
Section: Introductionmentioning
confidence: 99%
“…It is explicitly noted that soil moisture changes due to precipitation are well captured. The authors of [21] have even derived soil moisture at a 500 m resolution. In WaterSENSE, soil moisture is derived as part of the water cycle monitoring toolkit.…”
Section: Methods Extensions: Use Of Soil Moisture Datamentioning
confidence: 99%